High-energy, hundred-picosecond pulsed 266 nm mid-ultraviolet generation by a barium borate crystal - Ning Wen; Nan Wang; Nan Zong; Xue-Chun Lin; Hong-Wei Gao; Yong Bo; Qin-Jun Peng; Da-Fu Cui; Zu-Yan Xu (High Power Laser Science and Engineering, 2023)
We present a high-energy, hundred-picosecond (ps) pulsed mid-ultraviolet solid-state laser at 266 nm by a direct second harmonic generation (SHG) in a barium borate (BaB2O4, BBO) nonlinear crystal. The green pump source is a 710 mJ, 330 ps pulsed laser at a wavelength of 532 nm with a repetition rate of 1 Hz. Under a green pump energy of 710 mJ, a maximum output energy of 253.3 mJ at 266 nm is achieved with 250 ps pulse duration resulting in a peak power of more than 1 GW, corresponding to an SHG conversion efficiency of 35.7% from 532 to 266 nm. The experimental data were well consistent with the theoretical prediction. To the best of our knowledge, this laser exhibits both the highest output energy and highest peak power ever achieved in a hundred-ps/ps regime at 266 nm for BBO-SHG.